Antioxidant Activities of Ficus elastica Leaves Ethanol Extract and Its Compounds - Chrismis Novalinda Ginting; I Nyoman Ehrich Lister; Ermi Girsang; Dewi Riastawati; Hanna Sari Widya Kusuma; Wahyu Widowati (Molecular and Cellular Biomedical Sciences, 2020)
Background: The excessive free radicals condition called oxidative stress can harmful for the body. To prevent and cure it, the antioxidant agents are required. Nowadays, the natural product extracted from plants have been widely used in folk medicine as antioxidant for the treatment of many diseases. Ficus elastica (rubber tree) has some compounds that has several biological activities, i.e., quercitrin, myricitrin, morin, and eleutheroside B. The F. elastica works against the free radicals and can be potential as antioxidant agent. The purpose of this study was to evaluate antioxidant properties of F. elastica ethanolic extract (FEE), quercitrin, myricitrin, morin, and eleutheroside B.Materials and Methods: The antioxidant activities of FEE and standard compounds were evaluated by free radical-scavenging activity of 2,2-diphenyl-1-picrylhydrazil (DPPH), hydrogen peroxide (H2O2), 2,2’-azinobis-(3-ethylbenzothiazoline- 6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) activities using spectrophotometry method.Results: FEE has the lowest of DPPH scavenging activity (IC50=13.82 µg/mL) than other compounds. In ABTS scavenging activity, FEE has moderate activity with IC50 value 23.29 µg/mL. In FRAP activity, FEE has moderate activity with value 241.58 µM Fe(II)/µg, while in H2O2 scavenging activity, FEE also show moderate activity with IC50=83.97 µg/mL compared to other compounds.Conclusion: In summary, FEE and the pure compounds (quercitrin, myricitrin, morin, and eleutheroside B) have potential as antioxidant agent.Keywords: free radical, morin, myricitrin, quercitrin, rubber tree, scavenging activities